Preiskovalno načelo v delovnih sporih - Ciraj, Nataša (Delavci in delodajalci, 2020)
The paper addresses the aim of the principle of ex officio investigation, which represents a special procedural principle in the regulation of judicial proceedings in labour disputes. Through the analysis of common traits and differences of the principle of ex officio investigation in the Slovenian, Austrian, German and Swiss regulations, the manifestations of this principle within individual procedural tasks are presented as well as the carrying out of investigative judicial powers, their limitations and the relationship to material organisation of procedure. Through the theoretical starting points and analysis of case law, the significant effects of the principle of ex officio investigation are highlighted, by which the requirements of fair trial are fulfilled pursuant to Article 6 of the European Convention on Human Rights.
Keywords: acceleration of the procedure; delovni spori; delovno pravo; enakost orožij; equality of arms; examination of facts; izvajanje dokazov; labour disputes; pospešitev postopka; postopkovne posebnosti; pravica do poštenega postopka; preiskovanje dejstev; procedural principles; procesna načela; right to a fair trial; specific features of the procedure; taking of evidence